STRATEGI PEMBELAJARAN GURU KEAGAMAAN PADA MASA PANDEMI COVID-19 DI MTs MUSLIMAT NU PALANGKA RAYA - Jakirah Jakirah; Jasiah Jasiah; Marsiah Marsiah (FORUM PAEDAGOGIK, 2021)
AbstractThis study aims to examine the learning strategies used by the religious teachers of MTs Muslimat NU Palangka Raya during the Covid-19 pandemic. The research method used is a qualitative descriptive method The results of this study indicate that religious teachers at MTs Muslimat NU Palangka Raya use an online learning strategy by making teaching videos and creating a WhatsApp group to share videos, attendance, and assignments with students, as well as questions and answers regarding learning material that was unclear for students. Religious teachers in MTs Muslimat NU Palangkaraya run an online learning strategy with the supporting factor that all teachers and students have Hp, internet networks in schools, and all the teachers and students have app WhatsApp faced. The obstacle faced is that the teacher has difficulty checking student assignments because there are several students sending assignments at once not according to the assignment collection schedule. Keywords: covid-19, learning, pandemic, strategies. AbstrakPenelitian ini bertujuan untuk mengkaji strategi pembelajaran yang digunakan oleh guru keagamaan di MTs Muslimat NU Palangka Raya selama masa pandemi covid-19. Metode penelitian yang digunakan adalah metode deskriptif kualitatif. Hasil penelitian ini menunjukkan bahwa guru keagamaan di MTs Muslimat NU Palangka Raya menggunakan strategi pembelajaran daring dengan membuat video mengajar dan membuat group whatsapp untu berbagi video, absensi dan tugas kepada siswa, serta tanya jawab terkait materi pembelajaran yang kurang jelas. Guru keagamaan di MTs Muslimat NU Palangka Raya menerapkan strategi pembelajaran daring dengan faktor pendukung yaitu semua guru dan siswa memiliki Hp, ada internet di sekolah, dan semua guru dan siswa memiliki aplikasi whatsapp. Kendala yang dihadapi adalah guru kesulitan untuk mengecek tugas siswa karena ada beberapa siswa yang mengirimkan tugas secara bersamaan tidak sesuai dengan jadwal pengumpulan tugas. Kata kunci: covid-19, pandemi, pembelajaran, strategi.